Socio-economic analysis of the current state and prospects of development of the Zakarpattia region - Грицай, О. І.; Грицай, І. А.; Grytsay, O.; Hrytsai, I. (Видавництво Львівської політехніки, 2023)
Досліджено основні статистичні показники Закарпатської області: валовий регіональний продукт (ВРП), інфляцію, економічну активність населення, безробіття, рівень споживчих цін, капітальні вкладення, зовнішньоекономічну діяльність, видатки домогосподарств, рівень заробітної плати та доходів населення у 2007–2019 рр., динаміку яких відображають два кризові періоди: 2008 та 2014–2015 рр. Визначено пріоритетні напрями вдосконалення територіальної організації Закарпатської області, які забезпечать стійкість регіонального розвитку. Унікальне геополітичне розташування Закарпатської області та її аграрна спрямованість є вирішальними факторами для подолання криз та пожвавлення соціально-економічного розвитку регіону.

Purpose. The study’s purpose is a socio-economic analysis of the Zakarpattia region’s current state of development to determine the factors that affect the current situation and priority areas for improving the territorial organization Zakarpattia region, which will ensure sustainable regional development. Design/methodology/approach. In the article, the authors used the literature review method to identify the state of research on socio-economic development of the regions of Ukraine and to justify the importance of separate consideration of the dynamics of macroeconomic indicators. As a result of the analysis of scientific literature sources on the issue of socio-economic development of the Carpathian region of Ukraine, it was revealed that empirical studies of statistical data are insufficiently presented. Based on the comparative method, system analysis, and synthesis, the leading statistical indicators of the Zakarpattia region are studied: gross regional product (GRP), inflation, the economic activity of the population, unemployment, level of consumer prices, capital investments, foreign economic activity, household expenditures, level of wages and incomes of the people for 2007–2019, the dynamics of which reflects two crisis periods: 2008 and 2014–2015. Economic development dynamics in conditions of political instability and rapid changes in the external environment show positive macroeconomic changes reflected in GDP growth, wage growth, increasing exports, and the excess of exports over imports. Findings. The hypothesis that the focus of achieving the most efficient use of the region’s potential and its balanced development is possible only based on coordination of economic, social, and environmental interests, both at the regional and national levels. In particular, the study of GRP of the Zakarpattia region during 2007–2019 shows a stable growth of the area's nominal GRP. However, the real GRP at the same time, although fluctuating abruptly and in general, remains virtually unchanged. A study of the share of the Zakarpattia region’s economically active population in the structure of the economically active population of Ukraine allows us to conclude that it has changed unevenly and has tended to decrease. The border location of the Zakarpattia region facilitated emigration. In 2020, the share of the economically active population was declining, and unemployment is rising due to the loss of many people of their jobs due to the pandemic, which directly impacts reducing real and nominal GRP. Today’s economic recovery is taking place without significant changes in domestic enterprises’ quantitative structure by industry and is not accompanied by an increase in foreign investment. Practical implications. The results of this research are of interest to scientists and students of educational institutions, employees of research institutions that study the development trends of the regions of Ukraine. Besides, the results can help employees of public authorities of the Zakarpattia region shape the area’s development strategy. Originality/value. This study highlights the strengthening of globalization processes at the present stage of development of our state puts before its regions the main requirement – to maintain and streng then the positive growth of vital socio-economic indicators through the introduction of administrative, legal, tax, financial and other measures in the interests of the population and the state as a whole. The main factors influencing the socio-economic development of the Zakarpattia region are identified. Thus, based on the analysis, we can conclude that the Zakarpattia region’s socio-economic development will depend on the dynamics of production and consumption and improve the results of foreign economic activity. Priority areas for improving the Zakarpattia region’s territorial organization, which will ensure regional development sustainability, have been identified. The unique geopolitical location of Zakarpattia region and its agricultural orientation and tourism are decisive factors in overcoming crises and reviving its socio-economic development.
Соціально-економічний аналіз сучасного стану і перспектив розвитку Закарпатської області
Keywords: економічний розвиток регіону; ВРП; інфляція; економічна активність населення; безробіття; рівень споживчих цін; капітальні інвестиції; витрати домогосподарств; рівень заробітної плати та доходів населення; economic development of the region; GRP; inflation; the economic activity of the population; unemployment; level of consumer prices; capital investments; foreign economic activity; household expenditures; level of wages and incomes of the population; 332.145